Influence of shelterbelts on nitrous oxide emissions and denitrification enzyme activity in Manawatu pasture soils, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Soil Science, School of Agriculture and Environment, Massey University, Palmerston North, New Zealand - Yee, Nandar Hnin (Massey University, 2021)
Nitrification and denitrification are the important soil biological nitrogen (N) transformation processes that are major contributors to nitrous oxide (N₂O) emissions. In temperate pastoral soils, denitrification by microbial activity is the major producer of N₂O emissions. One of the potential mitigation options that could reduce greenhouse gas (GHG) emissions from pastoral systems is the use of shelterbelts, as these sequester carbon (C) in soil and biomass. Yet shelterbelts could also alter the N cycle and, therefore, prior to widely proposing the establishment of shelterbelts in New Zealand (NZ) pastoral systems to mitigate GHG emissions, their influence on soil N₂O emissions needs to be investigated. The objective of this study was to investigate whether shelterbelt establishment in animal grazed pastures provides an additional benefit of N₂O emission reduction in the Manawatu Region, NZ. To achieve these objectives, one laboratory incubation to measure denitrification enzyme activity (DEA) in soil samples taken from 5 paired sites in the Manawatu Region. The study farms were dairy farm (MF) - Massey University Dairy 4, dairy farm (SD) - Stewart Dairy Land, Ashurst, dairy farm (TF) - Table flat farm, Apiti, dairy farm (GO) - Glen Oroua, Rongotea and sheep and beef farm (TP) - Tuapaka Farm, Massey University. Field trials of N₂O measurements were conducted in two of these paired sites (MF and SD) during winter/autumn 2020. Soil physico-chemical characteristics were also assessed. At each farm, a control paddock (without shelterbelt) and a treatment paddock (with shelterbelt) were identified. Soils were taken at 0-10 cm depth from six distances (1, 5, 10, 20, 40, and 80 m) from the shelterbelt and from the roadside boundary of the paddock. Like DEA, field N₂O emission measurements were also carried out in two out of the five farms at the same above-mentioned distances. The results indicated that, there was a significant effect of shelterbelt on soil pH in all but one site, yet the trend was not consistent among sites. At three sites, a significantly higher soil water content was observed in soils under shelterbelt’s influence. In general, a higher NO₃⁻-N content accumulated at the shorter distance from the shelterbelt (1, 5, and 10 m) compared with farther away from trees (20, 40, and 80 m), while a lower soil NH₄⁺-N content was found closer to the trees. No significant influence of shelterbelt on DEA was detected except for one study site. Nitrous oxide emission was positively related to high NO₃⁻-N content. Out of the two study farms in which N₂O emissions were measured, the effect of the shelterbelt was only detected in one of them, with a significantly higher N₂O emission from non-shelterbelt soils than from shelterbelt soils. The two experiments of DEA and field N₂O emission have indicated that soil pH and NO₃⁻-N content are the main soil factors influencing denitrification and N₂O emission in this study soils. By reducing NO₃⁻-N content and modifying the pH value, especially in the close vicinity of trees, shelterbelts could reduce N loss by suppressing denitrification transformation processes in soils.
The following Figures were removed for copyright reasons: 2.1 (=Singh et al., 2019 Fig 7), 2.2 (= Saggar et al., 2013 Fig 1) & 2.4 (=Jämsén et al., 2015 Fig 2).
Keywords: 300204 Agricultural management of nutrients